1996
DOI: 10.1073/pnas.93.6.2420
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous avoidance behavior in Drosophila null for calmodulin expression.

Abstract: The regulatory protein calmodulin is a major mediator of calcium-induced changes in cellular activity. To analyze the roles of calmodulin in an intact animal, we have generated a calmodulin null mutation in Drosophila melanogaster. Maternal calmodulin supports calmodulin null individuals throughout embryogenesis, but they die within 2 days of hatching as first instar larvae. We have detected two pronounced behavioral abnormalities specific to the loss of calmodulin in these larvae. Swinging of the head and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 39 publications
0
39
1
Order By: Relevance
“…In Drosophila, CaM is encoded by a single gene, cam [170,171], and null mutations in cam are lethal [172]. Mosaic flies missing cam from the eye display developmental defects.…”
Section: Ca 2+ -Dependent Termination Of the Photoresponsementioning
confidence: 99%
“…In Drosophila, CaM is encoded by a single gene, cam [170,171], and null mutations in cam are lethal [172]. Mosaic flies missing cam from the eye display developmental defects.…”
Section: Ca 2+ -Dependent Termination Of the Photoresponsementioning
confidence: 99%
“…Calmodulin is encoded by essential genes in Drosophila melanogaster, Aspergillus nidulans, Saccharomyces cerevisiae, and Schizosaccharomyces pombe (13,23,30,42). Given that the cam1-ts mutant cells express less than 2% of the wild-type level of calmodulin mRNA, we sought to test if CAM1 is an essential gene and if this reduced level is sufficient to maintain cell viability or alternatively whether the CAM1 gene is dispensable for viability in C. neoformans at 25°C but required at 37°C.…”
Section: An Insertional Mutagenesis Screen For High-temperature Growtmentioning
confidence: 99%
“…Studies in yeast (9) and Drosophila (10) revealed that CaM is an indispensable gene. Although there is less sequence identity between yeast and animal CaMs (60% identity) than among most animal CaMs, human CaM could functionally complement yeast CaM (11).…”
mentioning
confidence: 99%